Perlawanan dan Pencarian Identitas: Eksplorasi Eksistensi Perempuan dalam Candid karya Tenni Purwanti (Kajian Feminis Eksistensialis Simone de Beauvoir) - Akhlaqul Karimah, Aisyah; Kamillia Khakim, Annisa (Humanis, 2025)
In the current era of progress, women continue to face discrimination, marginalization, and inequality in both domestic and public spheres. This research explores the forms and strategies of female existence in the short story Candid by Tenni Purwanti. Using Simone de Beauvoir’s existentialist theory and a qualitative descriptive approach, the study analyzes data from the short story Candid in the collection Sambal dan Ranjang. Data were collected through reading and note-taking techniques. The findings highlight three key concepts representing women: fate and history, myth, and contemporary female life. Women assert their existence by working, engaging intellectually, transforming socially, and rejecting dependence on men. Female characters such as Alisia, her mother, and her sister demonstrate that women are capable of living independently and enacting social change through resistance to patriarchal domination. This study affirms the continuing struggle of women to define their identity and autonomy within a patriarchal society.